Therapeutic advances in non-alcoholic fatty liver disease: A microbiota-centered view - Chen, Hui-Ting; Huang, Hong-Li; Li, Yong-Qiang; Xu, Hao-Ming; Zhou, Yong-Jian (World journal of gastroenterology : WJG, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent metabolic disorder with steadily increasing incidence rates worldwide, especially in the West. There are no drugs available at present to treat NAFLD, and the primary therapeutic options include weight loss and the combination of healthy diet and exercise. Therefore, novel interventions are required that can target the underlying risk factors. Gut microbiota is an "invisible organ" of the human body and vital for normal metabolism and immuno-modulation. The number and diversity of microbes differ across the gastrointestinal tract from the mouth to the anus, and is most abundant in the intestine. Since dysregulated gut microbiota is an underlying pathological factor of NAFLD, it is a viable therapeutic target that can be modulated by antibiotics, probiotics, prebiotics, synbiotics, fecal microbiota transplantation, and microbial metabolites. In this review, we summarize the most recent advances in gut microbiota-targeted therapies against NAFLD in clinical and experimental studies, and critically evaluate novel targets and strategies for treating NAFLD.